Analysis of Supporting Factors for the Establishment of Bumdes “Tunas Mekar” in Realizing the Welfare of the Communities of Afdeling II Village, Bilah Barat, Labuhanbatu District - Agustin, Rina; Simanjorang, Elida Florentina Sinaga; Harahap, Aziddin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
BUMDes is a business institution managed by the community and village government to strengthen the village economy and build community social cohesion which is formed based on village needs and potential. BUMDes Mekar Sari is one of the BUMDes that has developed, which manages the business of selling Pertamax-92 fuel oil (BBM), through Pertamina’s Pertashop, and Coffee and Culinary Stalls. This study aims to describe the supporting factors for the establishment of BUMDes Tunas Mekar in realizing the welfare of the people of Afdeling II village, West Bilah, Labuhanbatu Regency. The research method used in this study is a qualitative descriptive research method, to explore, explore, and describe the research results in a description of the words. The data collection techniques are carried out by observation, interviews, and documentation/literature studies. In this study, the f factors that influenced the establishment of Mekar Sari BUMDes in realizing the welfare of the people of Afdeling II Bilah Barat Village included community participation, availability of initial capital, support from the Afdeling II Bilah Barat village government, and good leadership of the director of BUMDes Tunas Mekar.